Signs of connective tissue dysplasia in women with genital prolapse - A. S. Ustyuzhina; M. A. Solodilova; A. V. Polonikov; S. P. Pakhomov; U. G. Shokirova (IRBIS LLC, 2021)
Introduction. Despite a long history of the disease, genital prolapse still have not been definitively solved. A relevance of pelvic organ prolapse in women has been increasing in recent years largely due to a change in the quality of life and desire to sustain their youth. The number of studies pinpointing the cause of the disease in connective tissue dysplasia (CTD) has been increasing annually.Aim: to conduct a systematic analysis and determine most common signs of CTD in women with genital prolapse.Materials and methods. CTD criteria and the relationship with genital prolapse were analyzed. The study was conducted using questionnaires and including clinical studies examining residents of the Belgorod region (135 women). The main group included 91 patients who had signs of pelvic organ prolapse, and control group consisted of 44 healthy women. CTD intensity score proposed by T.Yu. Smolnova et al. (2003) was used to assess signs of dysplasia in women examined allowing to build up three groups in which each symptom was evaluated as severity score.Results. Asthenic constitution was noted in high percentage of women suffering from genital prolapse (16.70 ± 0.38 %) compared with healthy women (2.30 ± 0.15 %; p = 0.016). Mild bruising, increased tissue bleeding tended to rise in main vs. control group (16.50 ± 0.37 % in main group and 0.0 in control group; p = 0.016). Signs of varicose veins and hemorrhoids requiring no surgical treatment were found in 33.00 ± 0.47 % and 4.50 ± 0.21 % in main vs. control group (p = 0.0002), respectively. Genital prolapse and hernia in first-line relatives were recorded in 9.90 ± 0.30 % in main group (p = 0.031), women without signs of prolapse did not indicate prolapse in close relatives.Conclusion. Asthenic constitution, hernias, varicose veins and hemorrhoids, female pelvic and hernial prolapse in close female relatives, a tendency to mild bruising, skeletal anomalies, elastosis skin were among common CTD signs in women with genital prolapse.